In Elimination Settings, Measles Antibodies Wane After Vaccination but Not After Infection: A Systematic Review and Meta-Analysis . (13th April 2022) - Bolotin, Shelly; Osman, Selma; Hughes, Stephanie L; Ariyarajah, Archchun; Tricco, Andrea C; Khan, Sumaiya; Li, Lennon; Johnson, Caitlin; Friedman, Lindsay; Gul, Nazish; Jardine, Rachel; Faulkner, Maryrose; et al.
Abstract: Background: We conducted a systematic review to assess whether measles humoral immunity wanes in previously infected or vaccinated populations in measles elimination settings. Methods: After screening 16 822 citations, we identified 9 articles from populations exposed to wild-type measles and 16 articles from vaccinated populations that met our inclusion criteria. Results: Using linear regression, we found that geometric mean titers (GMTs) decreased significantly in individuals who received 2 doses of measles-containing vaccine (MCV) by 121.8 mIU/mL (95% confidence interval [CI], −212.4 to −31.1) per year since vaccination over 1 to 5 years, 53.7 mIU/mL (95% CI, −95.3 to −12.2) 5 to 10 years, 33.2 mIU/mL (95% CI, −62.6 to −3.9), 10 to 15 years, and 24.1 mIU/mL (95% CI, −51.5 to 3.3) 15 to 20 years since vaccination. Decreases in GMT over time were not significant after 1 dose of MCV or after infection. Decreases in the proportion of seropositive individuals over time were not significant after 1 or 2 doses of MCV or after infection. Conclusions: Measles antibody waning in vaccinated populations should be considered in planning for measles elimination. Abstract : This review assesses whether humoral immunity from measles vaccine or infection wanes over time. Antibody levels in individuals receiving 2 doses of MCV declined nonlinearly over the 20 years of available data but did not fall below the protective threshold.